The Reliability of Clock Drawing Test Scoring Systems Modeled on the Normative Data in Healthy Aging and Nonamnestic Mild Cognitive Impairment. (October 2017) - Mazancova, Adela Fendrych; Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Bezdicek, Ondrej
The Clock Drawing Test (CDT) is a commonly used tool in clinical practice and research for cognitive screening among older adults. The main goal of the present study was to analyze the interrater reliability of three different CDT scoring systems (by Shulman et al., Babins et al., and Cohen et al.). We used a clock with a predrawn circle. The CDT was evaluated by three independent raters based on the normative data set of healthy older and very old adults and patients with nonamnestic mild cognitive impairment (naMCI; N = 438; aged 61-94). We confirmed a high interrater reliability measured by the intraclass correlation coefficients (ICCs): Shulman ICC = .809, Babins ICC = .894, and Cohen ICC = .862, all p < .001. We found that age and education levels have a significant effect on CDT performance, yet there was no influence of gender. Finally, the scoring systems differentiated between naMCI and age- and education-matched controls: Shulman's area under the receiver operating characteristic curve (AUC) = .84, Cohen AUC = .71, all p < .001; and a slightly lower discriminative ability was shown by Babins: AUC = .65, p = .012.